ANALISIS FAKTOR RATA-RATA LAMA SEKOLAH DAN PENGANGGURAN TERBUKA DALAM MEMPENGARUHI TINGKAT KEMISKINAN DI KABUPATEN SUMBAWA - Rahim, Abdul; Haryadi, Wahyu; Muliawansyah, Dandung (Pusat Riset dan Publikasi, 2024)
This study aims to analyze the factors of average length of schooling and open unemployment in influencing the poverty rate in Sumbawa District in 2010-2020. The type of this study was associative. The type of data used in this study was secondary data obtained from documents contained in the Sumbawa District Central Statistics Agency. Data analysis was performed using multiple linear regression analysis techniques, partial and simultaneous hypothesis testing, and the coefficient of determination (R2) testing through SPSS software version 16.0 for windows. Based on the results of the tests showed that (1) the average length of schooling partially had a negative and significant effect on the poverty rate in Sumbawa District, (2) the open unemployment partially had a positive and significant effect on the poverty rate in Sumbawa District, (3) The average length of schooling and open unemployment simultaneously had a significant effect on the poverty rate in Sumbawa District. The ability of the variables average length of schooling and open unemployment to influence changes in poverty levels in Sumbawa District was 94.8%, while the remaining 5.2% was influenced by other variables outside this research model, such as education, GRDP and Minimum Wage.